Analysis IT Governance of Perumdam Tirta Siak using COBIT 2019 and ISO27001 - Sari, Mayang; Andriyani, Yanti; Id, Ibnu Daqiqil; Sukamto, Sukamto (Sistemasi: Jurnal Sistem Informasi, 2024)
Perumdam Tirta Siak Pekanbaru (PDAM) is a local government company responsible for the management and fulfillment of water needs. PDAM currently uses information technology to provide excellent service to customers. The Institute of Directors Report explains that a company has good IT governance if it focuses on risk management and resource management, value fulfillment, and strategic alignment. The level of IT capability in supporting the company's performance can be known through evaluation activities on the current IT implementation. Evaluation is important to determine the level of IT capability in supporting company performance in accordance with the objectives. Thus, this study aims to evaluate information technology governance through an analysis process using the COBIT 2019 framework and the ISO/IEC 27001 standard with process objectives APO14 - Managed Data and BAI06 - Managed IT Changes. The results showed that the current level of IT implementation capability in objective APO14 - Managed Data and BAI06 - Managed IT Changes is at level 2, namely the process has been running but there are still a number of activities that have not been carried out properly. There is a gap between the current capability level and the desired capability level of 1 level (APO14) and 2 levels (BAI06). Thus, 15 improvement recommendations are proposed that refer to the ISO / IEC 27001 standard to create IT governance that is effective, efficient and aligned with company goals.